Breaking the Commodity Trap: Exploring Consumers Paying More for Soto in Premium Local Restaurants in the Jabodetabek Area, A Means-End Chain Study - derry rinaldi; Tengku Ezni Balqiah (Sekolah Tinggi Manajemen IPMI, 2026)
This study examined the cognitive structures underlying consumers' willingness to pay premium prices for traditional Indonesian soto in premium casual dining restaurants. Using Means-End Chain (MEC) methodology, in-depth laddering interviews were conducted with 10 urban professionals aged 25-45 at Assistant Manager level and above in Jabodetabek. NVivo 12 analysis identified 104 unique codes with 12 core codes appearing in ≥90% of respondents. The findings revealed four dominant cognitive pathways: (1) Comfort-Security-Occasion route, (2) Quality-Authenticity-Price Boundary route, (3) Service-Family Care route, and (4) Value-Fairness-Price Boundary route. Security emerged as the central terminal value, appearing in three of four pathways, challenging Western MEC literature where happiness or status typically dominate. The study introduced the concept of